2017
DOI: 10.1158/1078-0432.ccr-16-0967
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Differences between Screen-Detected and Interval Breast Cancers Are Largely Explained by PAM50 Subtypes

Abstract: Interval breast cancer is of clinical interest, as it exhibits an aggressive phenotype and evades detection by screening mammography. A comprehensive picture of somatic changes that drive tumors to become symptomatic in the screening interval can improve understanding of the biology underlying these aggressive tumors. Initiated in April 2013, Clinical Sequencing of Cancer in Sweden (Clinseq) is a scientific and clinical platform for the genomic profiling of cancer. The breast cancer pilot study consisted of wo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
(46 reference statements)
3
17
0
Order By: Relevance
“…The only study that has reported associations between PAM50 results and mode of detection was based within a clinical cancer sequencing study in Sweden with 173 patients. That study had similar findings, showing that interval cancer was associated with basal-like subtype(19). Higher ROR-PT among interval cancers has not been assessed previously.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The only study that has reported associations between PAM50 results and mode of detection was based within a clinical cancer sequencing study in Sweden with 173 patients. That study had similar findings, showing that interval cancer was associated with basal-like subtype(19). Higher ROR-PT among interval cancers has not been assessed previously.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have shown that interval cancers have a more aggressive profile with respect to clinical factors such as estrogen receptor (ER), progesterone receptor (PR), or human epidermal growth factor (HER)2-status(8,13), but only one study has reported associations between interval cancer and RNA-based genomic subtype such as the PAM50 intrinsic subtype(19). No study to our knowledge has reported associations for the genomic risk of recurrence (ROR-PT) score based on PAM50.…”
Section: Introductionmentioning
confidence: 99%
“…first reported that these two types of breast cancer may have unique underlying biology based on a 77 single-nucleotide polymorphism risk score However, a recent, well-designed study indicated molecular differences between less aggressive screening-detected breast cancer and more aggressive ICs. The two diseases are biologically distinct in terms of somatic mutations, copy number aberrations, and gene expression, but most of these differences are no longer significant after adjusting for breast cancer subtypes and mammography density (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite that, interval cancers have been reported to have a similar survival as cancers diagnosed among women not participating in screening [36, 37]. This observation is somewhat contradictory to the common belief that interval cancers have a more aggressive molecular phenotype and a faster growth rate [23, 32, 38]. This also challenges the theory of a strong correlation between growth rate and metastatic potential, and the belief that patients with interval cancers should receive more aggressive treatment [36, 37].…”
Section: Discussionmentioning
confidence: 99%